2017
DOI: 10.3844/jcssp.2017.78.90
|View full text |Cite
|
Sign up to set email alerts
|

Scrutiny of Relationship between E-Banking Information Quality Dimensions and Customer Satisfaction

Abstract: Poor information quality can have a significant negative effect on the success of an organization. This study investigated the relationship between information quality's dimensions, namely accuracy, completeness, timeliness and relevancy, on the satisfaction of customers towards E-banking services in Palestine's banking sector. It also studied the relationship between the intent to use E-banking services and customer satisfaction. The study implemented a quantitative method for data collection using a question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 66 publications
0
14
0
1
Order By: Relevance
“…DeLone and McLean [5] proposed a famous information system success model known as the D&M model that has the ability to measure system standards, and this model has been theoretically and empirically developed and improved in several studies [18,19]. For example, Bernroider [20] applied the D&M model to measure the effectiveness of adopting ERP in different sizes of companies from the perspective of information technology.…”
Section: Statistical Methods For the Dandm Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…DeLone and McLean [5] proposed a famous information system success model known as the D&M model that has the ability to measure system standards, and this model has been theoretically and empirically developed and improved in several studies [18,19]. For example, Bernroider [20] applied the D&M model to measure the effectiveness of adopting ERP in different sizes of companies from the perspective of information technology.…”
Section: Statistical Methods For the Dandm Modelmentioning
confidence: 99%
“…The result showed that system quality and service quality had a positive influence on intention to use the cloud e-bookcase and user satisfaction. Ayyash [18] developed four dimensions (accuracy, timeliness, completeness, and relevancy) used to reflect information quality, and discussed the relationship between these four dimensions and customer satisfaction in the e-banking industry.…”
Section: Statistical Methods For the Dandm Modelmentioning
confidence: 99%
See 3 more Smart Citations